Law and practice of international commercial arbitration - Redfern, Alan (Sweet & Maxwell LondonGB, 1991)
Provides a comprehensive review of the process of internatioanl commerical arbitration from beginning to end - from the drafting of the arbitration agreement to the enforcement of the arbitral tribunal's award. Describes the role of the international arbitral institutions. Comments on institutional and international rules of arbitration as well as ad hoc arbitration.